Reciprocal strength ratio in shoulder abduction/adduction in sports and daily living - Mayer, F.; Axmann, D.; Horstmann, T.; Martini, F.; Fritz, J.; Dickhuth, H. H. (Medicine & Science in Sports & Exercise, 2001)
Purpose: Functionally, the shoulder is considered a ball joint, whereby high mobility is attended by low stability. Therefore, muscular balance is decisive for stability. Altered strength ratios are frequently described as "muscular dysbalances" and considered one of the causes of shoulder pathologies, whereby objective quantification is difficult. Methods: In order to quantify physiological muscle balance, the strength ratio of shoulder abduction/adduction (AB/AD) was determined in 166 untrained men (UM) concentrically at 60 degrees.s-1 (LIDO-Active). The influence on this norm of one-sided (25 high-performance (TPH), 18 leisure tennis players (TPL)) and two-sided athletic exercise (32 gymnasts (GY)), altered daily exercise (11 paraplegics with paralysis time < 4 months (PP), 11 paraplegics with paralysis time > 2 yr (PU)), and a combination of altered daily exercise and athletic activity (16 trained paraplegics (PT)) was examined (ANOVA, alpha = 0.05). Results: Determination of the AB/AD quotient in UM was 0.82. Shoulder stress in sports led to a decrease in quotients compared with UM because of a relatively increased torque in AD (P < 0.01). At the beginning of a paraplegia, the quotient of AB/AD is elevated (P < 0.05). This altered ratio decreases with duration of paralysis (PU) and athletic activity (PT). Conclusion: With increased shoulder stress, the altered strength ratios reflect specific requirements of the performance attained. However, the importance of muscular dysbalances for the onset of shoulder complaints must be considered more important than their influence on athletic performance capacity.